2020
DOI: 10.5334/aogh.2956
|View full text |Cite
|
Sign up to set email alerts
|

How Frequently Do We Touch Facial T-Zone: A Systematic Review

Abstract: Background: Researchers across the world are emphasising the importance of hand-washing and limited touching of face to curb the spread of COVID-19. However, access to safe water and hygiene is inadequate in many places around the globe; hence T-zone touching restriction is considered more worthwhile compared to other prevention strategies. Aim: A systematic review was carried out to appraise the frequency of T-zone (eyes, nose, mouth, chin) touching in humans to compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 28 publications
0
23
1
Order By: Relevance
“…The transfer of DNA from face to hands may depend on personal habits such as the frequency of touching or scratching facial parts. It has been reported that people touch their face on average 50 times per hour [34]. Thus, even if some individuals tend to touch their face less than others, it seems that independently of such differences a person with a high release of DNA from the face also is more likely to deposit high amounts from the hands.…”
Section: Discussionmentioning
confidence: 99%
“…The transfer of DNA from face to hands may depend on personal habits such as the frequency of touching or scratching facial parts. It has been reported that people touch their face on average 50 times per hour [34]. Thus, even if some individuals tend to touch their face less than others, it seems that independently of such differences a person with a high release of DNA from the face also is more likely to deposit high amounts from the hands.…”
Section: Discussionmentioning
confidence: 99%
“…In the restaurant, diners, on average, touched surfaces 450 times per hour and staff members touched surfaces 761 times per hour owing to their frequent service. Touching mucous membranes (T-zone), which is influenced by occupations and indoor environments, plays the most critical role in infection risk ( Kwok et al, 2015 ;Rahman et al, 2020 ). Postgraduate students in offices touched their mucous membranes 35.0 times per hour ( Zhang et al, 2021d ).…”
Section: Discussionmentioning
confidence: 99%
“…Clusters of infection played an important role. Frequently touching the T-zone (eyes, nose, mouth, chin) increases the chance of COVID-19 infection[ 16 ]. Transmission from an asymptomatic/pre-symptomatic patient is possible and more significant with pre-symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%